Saas-Fee Advanced Courses
DOI: 10.1007/978-3-540-30310-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Microlensing

Abstract: This review forms the microlensing part of the 33rd Saas-Fee Advanced Course "Gravitational Lensing: Strong, Weak & Micro'', which was held in April 2003 in Les Diablerets. It contains an introduction to the lensing effects of single and binary stars and it summarizes the state-of-the-art of microlensing observations and prospects at the time of the meeting. Stellar microlensing as well as quasar microlensing are covered.Comment: 93 pages, 51 figures; to appear (April 2006) in: Kochanek, C.S., Schneider, P.,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(33 citation statements)
references
References 60 publications
0
32
0
1
Order By: Relevance
“…Direct probes of the sub-microarcsecond structure of AGNs have been therefore limited to very long baseline interferometry studies of the radio-emitting regions, gravitational microlensing studies of the accretion disk (see review by Wambsganss 2006), and reverberation mapping of the broad-line regions (BLRs; Blandford & McKee 1982;Peterson 1993). The technique of reverberation mapping (a.k.a.…”
Section: Introductionmentioning
confidence: 99%
“…Direct probes of the sub-microarcsecond structure of AGNs have been therefore limited to very long baseline interferometry studies of the radio-emitting regions, gravitational microlensing studies of the accretion disk (see review by Wambsganss 2006), and reverberation mapping of the broad-line regions (BLRs; Blandford & McKee 1982;Peterson 1993). The technique of reverberation mapping (a.k.a.…”
Section: Introductionmentioning
confidence: 99%
“…Sources that are smaller than the Einstein radius of the stars, typically ∼10 16 cm, show time variable fluxes whose amplitude is determined by the source size (see the review by Wambsganss 2006). Smaller sources have larger variability amplitudes than larger sources.…”
Section: Introductionmentioning
confidence: 99%
“…Gravitational microlensing (Chang & Refsdal 1979, 1984; see also Kochanek 2004 andWambsganss 2006) is the main tool used to estimate both parameters, either from time variability or through the wavelength dependence of the microlensing magnification. Microlensing studies (see e.g., Pooley et al 2007;Morgan et al 2010;Blackburne et al 2011Blackburne et al , 2014Blackburne et al , 2015Sluse et al 2011;Jiménez-Vicente et al 2012Hainline et al 2013;Mosquera et al 2013;MacLeod et al 2015) have found that the mean sizes of quasar accretion disks are roughly a factor of 2-3 greater than the predictions of the standard thin disk model.…”
Section: Introductionmentioning
confidence: 99%